How do you solve \frac { 2} { 3} ( n + 5) = \frac { 3} { 4} ( n - 1)?

1 Answer
Apr 12, 2018

n = 49

Explanation:

You have to isolate the "n" terms and bring them to the side of the equation.

But first you get rid of the fractions on both sides by multiplying the left hand side by 4 and the right hand side by 3.

2/3 (n + 5) = 3/4 (n - 1)

4*2 (n + 5) = 3*3 (n - 1)

8 (n + 5) = 9 (n - 1)

Multiply out the brackets and

8 n + 40 = 9 n - 9

And bring n to the right hand side.

40 + 9 = 9 n - 8 n

n = 49